Inferior vena cava diameter and collapsibility index as a marker of fluid status in regular hemodialysis patients - Mohamed Abd El Hamid Hafiz; Emad Allam Mohamed; Mohamed Abo El Naga Mohamed; Mohamed Ahmed El Sayed Ahmed (SpringerOpen, 2021)
Abstract Background Patients with renal failure suffer from fluid overload which is a risk factor for mortality and morbidity. Therefore, fluid status assessment in patients on regular hemodialysis is very important. Dry weight assessment by clinical parameters is not always reliable. We evaluate the role of inferior vena cava ultrasound in estimating fluid overload in regular hemodialysis patients. Results A total of 45 persons, 30 end-stage renal disease patients on regular hemodialysis in group A (18 men and 12 women) and 15 healthy persons in group B (10 men and 5 women), were included in the study. The patients in group A ages ranged from 29 to 70 years with a mean of 48.38 ± 12.70 years and in group B ages ranged from 25 to 55 years with a mean of 34.93 ± 8.26. By clinical methods, the mean dry weight was 68.37 kg (68.37 ± 10.42). After HD mean, IVCe decreased from 2.01 ± 0.29 to 1.79 ± 0.22 cm (P < 0.001) similarly, mean IVCi decreased from 0.99 ± 0.48 to 0.64 ± 0.39 cm (P < 0.001). Changes in IVCD were significantly correlated with alterations in body weight following dialysis (P < 0.001). The IVC-CI increased significantly after dialysis (P < 0.001). IVCD and its IVC-CI reflected alterations in fluid status (P < 0.001). Considering the clinical parameters of fluid status, following HD mean, heart rate increased from 81.80 ± 5.15 beats per minute to 89.87 ± 6.42, (P < 0.001), systolic blood pressure decreased from 130 ± 18.43 mmHg to 113.33 ± 15.27 (P < 0.001), and diastolic blood pressure decreased from 80.17 ± 10.12 mmHg to 71.50 ± 9.29 (P < 0.001). Conclusion It was found a significant correlation between IVCD and IVC-CI with ultrafiltration of hemodialysis. Thus, IVC ultrasound can be used in dry weight assessment in ESRD patients on regular HD by measurement of IVCD and IVC-CI before and after hemodialysis.